Toward Cove-Edged Low Band Gap Graphene Nanoribbons - Liu, Junzhi; Li, Bo-Wei; Tan, Yuan-Zhi; Giannakopoulos, Angelos; Sanchez-Sanchez, Carlos; Beljonne, David; Ruffieux, Pascal; Fasel, Roman; Feng, Xinliang; Muellen, Klaus (Journal of the American Chemical Society, 2015)
Graphene nanoribbons (GNRs), defined as nanometer-wide strips of graphene, have attracted increasing attention as promising candidates for next-generation semiconductors. Here, we demonstrate a bottom-up strategy toward novel low band gap GNRs (Eg = 1.70 eV) with a well-defined cove-type periphery both in solution and on a solid substrate surface with chrysene as the key monomer. Corresponding cyclized chrysene-based oligomers consisting of the dimer and tetramer are obtained via an Ullmann coupling followed by oxidative intramolecular cyclodehydrogenation in solution, and much higher GNR homologues via on-surface synthesis. These oligomers adopt nonplanar structures due to the steric repulsion between the two C-H bonds at the inner cove position. Characterizations by single crystal X-ray analysis, UV-vis absorption spectroscopy, NMR spectroscopy, and scanning tunneling microscopy (STM) are described. The interpretation is assisted by density functional theory (DFT) calculations. (Figure Presented).
CRIS-Team Scopus Importer:2023-03-20